Ôn tập chương 1

bài 1 tính

-2^3.(3/4-0,25):(9/4-7/6)

bài 2 tìm x

a, $4\frac{1}{3}$:$\frac{x}{4}$=6:0,3

b,(23:4).2(x+1)=64

1 tháng 11 2019 lúc 18:13

Bài 1:

$\left(-2\right)^3.\left(\frac{3}{4}-0,25\right):\left(\frac{9}{4}-\frac{7}{6}\right)$

$=\left(-8\right).\left(\frac{3}{4}-\frac{1}{4}\right):\left(\frac{9}{4}-\frac{7}{6}\right)$

$=\left(-8\right).\frac{1}{2}:\frac{13}{12}$

$=\left(-4\right):\frac{13}{12}$

$=-\frac{48}{13}.$

Bài 2:

a) $4\frac{1}{3}:\frac{x}{4}=6:0,3$

$\Rightarrow\frac{13}{3}:\frac{x}{4}=6:0,3$

$\Rightarrow\frac{\frac{13}{3}}{\frac{x}{4}}=\frac{6}{0,3}$

$\Rightarrow\frac{13}{3}.0,3=6.\frac{x}{4}$

$\Rightarrow\frac{13}{10}=6.\frac{x}{4}$

$\Rightarrow\frac{x}{4}=\frac{13}{10}:6$

$\Rightarrow\frac{x}{4}=\frac{13}{60}$

$\Rightarrow x.60=13.4$

$\Rightarrow x.60=52$

$\Rightarrow x=52:60$

$\Rightarrow x=\frac{13}{15}$

Vậy $x=\frac{13}{15}.$

b) $\left(2^3:4\right).2^{x+1}=64$

$\Rightarrow\left(2^3:2^2\right).2^{x+1}=64$

$\Rightarrow2^1.2^{x+1}=64$

$\Rightarrow2^1.2^{x+1}=2^6$

$\Rightarrow1+x+1=6$

$\Rightarrow\left(1+1\right)+x=6$

$\Rightarrow2+x=6$

$\Rightarrow x=6-2$

$\Rightarrow x=4$

Vậy $x=4.$

Chúc em học tốt!

Bình luận (0)
1 tháng 11 2019 lúc 20:21

(−2)3.(34−0,25):(94−76)(−2)3.(34−0,25):(94−76)

=(−8).(34−14):(94−76)=(−8).(34−14):(94−76)

=(−8).12:1312=(−8).12:1312

=(−4):1312=(−4):1312

=−4813.=−4813.

Bài 2:

a) 413:x4=6:0,3413:x4=6:0,3

⇒133:x4=6:0,3⇒133:x4=6:0,3

⇒133x4=60,3⇒133x4=60,3

⇒133.0,3=6.x4⇒133.0,3=6.x4

⇒1310=6.x4⇒1310=6.x4

⇒x4=1310:6⇒x4=1310:6

⇒x4=1360⇒x4=1360

⇒x.60=13.4⇒x.60=13.4

⇒x.60=52⇒x.60=52

⇒x=52:60⇒x=52:60

⇒x=1315⇒x=1315

Vậy x=1315.x=1315.

b) (23:4).2x+1=64(23:4).2x+1=64

⇒(23:22).2x+1=64⇒(23:22).2x+1=64

⇒21.2x+1=64⇒21.2x+1=64

⇒21.2x+1=26⇒21.2x+1=26

⇒1+x+1=6⇒1+x+1=6

⇒(1+1)+x=6⇒(1+1)+x=6

⇒2+x=6⇒2+x=6

⇒x=6−2⇒x=6−2

⇒x=4⇒x=4

Vậy x=4.x=4.

Bình luận (0)

Các câu hỏi tương tự